Fluorine-containing micro-block polyaralkyl anion exchange membrane and preparation method thereof
By adopting fluorine-containing microblock polyaralkyl structure in the anion exchange membrane and using block copolymerization of hydrophobic and hydrophilic groups, the problem of low conductivity of the anion exchange membrane is solved, and the conductivity and mechanical properties are improved. It is suitable for fuels Efficient application of batteries.
Patent Information
- Application Number
- CN202411231730.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-01-10
AI Technical Summary
The low conductivity of anion exchange membrane limits the performance and application of fuel cells.
The preparation method of fluorine-containing microblock polyaralkyl anion exchange membrane is adopted. Through the block copolymerization of hydrophobic oligomers and hydrophilic oligomers, strong hydrophobic and strong hydrophilic groups are introduced, and the microphase is promoted by thermodynamic incompatibility. Separation to improve ionic conductivity.
It significantly improves the ion conductivity of the anion exchange membrane, enhances mechanical strength and temperature stability, and meets the efficient operation needs of fuel cells.
Smart Images

Figure CN119286021A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ion exchange membranes, and in particular to a fluorine-containing micro-block polyarylalkyl anion exchange membrane and a preparation method thereof. Background Art
[0002] Anion exchange membrane fuel cells (AEMFCs) are hailed as the most promising power generation technology to replace proton membrane fuel cells (PEMFCs) in the future due to their low redox overpotential, the use of non-precious metal catalysts, and simple water management. They are expected to alleviate the high cost problem of PEMFCs, which has reached technical saturation, and break through technical limitations. Anion exchange membranes (AEMs) are the "heart" component of AEMFCs, and their performance is crucial to the entire battery. However, the development and utilization of AEMs face the problem of low conductivity. Summary of the invention
[0003] The problem solved by the invention is how to solve the problem of low conductivity of anion exchange membrane.
[0004] In order to solve the above problems, the present invention provides a fluorine-containing micro-block polyarylalkyl anion exchange membrane and a preparation method thereof.
[0005] In a first aspect, the present invention provides a method for preparing a fluorinated microblock polyarylalkyl anion exchange membrane, which specifically comprises the following steps:
[0006] S1: dissolving biphenyl and trifluoroacetone in dichloromethane, then adding a superacid catalyst in an ice bath, stirring and reacting for more than 2 hours to obtain a hydrophobic oligomer;
[0007] S2: dissolving biphenyl and 7-bromo-1,1,1,-trifluoro-2-heptanone in dichloromethane, then adding a superacid catalyst in an ice bath, stirring and reacting for more than 2 hours to obtain a hydrophilic oligomer;
[0008] S3: mixing the hydrophobic oligomer and the hydrophilic oligomer for reaction for more than 6 hours to obtain a block copolymer solution, adding methanol for precipitation, filtering out the precipitate, and obtaining a fluorine-containing microblock polyarylalkyl copolymer including a hydrophilic segment and a hydrophobic segment;
[0009] S4: dissolving the fluorinated micro-block polyarylalkyl copolymer in N-methylpyrrolidone, and then adding 6-dimethylhexylaminotrimethylammonium iodide, reacting for more than 20 hours, and grafting the hydrophilic segment with a diquaternary ammonium cationic side chain. After the reaction, pouring into anhydrous ether solution to precipitate, filtering, and obtaining a quaternized fluorinated micro-block polyarylalkyl polymer;
[0010] S5: dissolving the quaternized fluorinated microblock polyarylalkyl polymer in dimethyl sulfoxide to obtain a uniform polymer membrane liquid, coating the polymer membrane liquid uniformly on a flat plate and drying it to obtain a block copolymerized fluorinated microblock polyarylalkyl anion exchange membrane.
[0011] Optionally, in step S1, the longer the stirring reaction time is, the longer the length of the hydrophobic oligomer is; in step S2, the longer the stirring reaction time is, the longer the length of the hydrophilic oligomer is.
[0012] Optionally, step S3 further includes: washing the precipitate with methanol for 3-5 times until the precipitate is neutral.
[0013] Optionally, the reaction is carried out at 60° C. for more than 20 hours in step S4.
[0014] Optionally, in step S5, the polymer film liquid is evenly coated on the flat plate and dried at 60-80° C. for more than 24 hours.
[0015] Optionally, the method further comprises step S6: soaking the fluorinated micro-block poly(arylalkyl) anion exchange membrane in a 1M NaOH solution for more than 24 hours, and then washing with deionized water to obtain a hydroxide-type fluorinated micro-block poly(arylalkyl) anion exchange membrane.
[0016] In a second aspect, the present invention provides a fluorine-containing microblock polyarylalkyl anion exchange membrane, which is prepared according to the preparation method of the fluorine-containing microblock polyarylalkyl anion exchange membrane as described above, and includes a microblock polymer main chain composed of a hydrophilic segment and a hydrophobic segment, the hydrophilic segment is grafted with a diquaternary ammonium cation side chain, and the hydrophobic segment contains superhydrophobic fluorine.
[0017] Optionally, the length of the hydrophilic segment and the hydrophobic segment can be regulated to increase the thermodynamic incompatibility between the hydrophilic segment and the hydrophobic segment, thereby regulating the microphase separation morphology and ion channel size of the fluorinated microblock polyarylalkyl anion exchange membrane.
[0018] Optionally, the tensile strength is 25.2-27.5 MPa, and the elongation at break is 12.6-14.9%.
[0019] Optionally, OH at 30°C - The conductivity is 28.76-42.50mS / cm. As the temperature rises to 80℃, OH - The conductivity increased to 94.49-132.70 mS / cm.
[0020] The beneficial effects of the fluorinated microblock polyarylalkyl anion exchange membrane and the preparation method thereof of the present invention are as follows: the hydrophobic segment formed by the hydrophobic oligomer is used to maintain the mechanical strength of the anion exchange membrane (AEMs), and the hydrophilic segment formed by the hydrophilic oligomer is grafted with a diquaternary ammonium cationic side chain by adding 6-dimethylhexylaminotrimethylammonium iodide to form a hydrophilic segment for OH- High-speed transmission of AEMs can be achieved by designing block copolymers of hydrophobic oligomers and hydrophilic oligomers, and the thermodynamic incompatibility between the hydrophilic and hydrophobic segments can be utilized to promote the microphase separation of AEMs and further improve the ionic conductivity. For the hydrophobic segment, the addition of trifluoroacetone and 7-bromo-1,1,1,-trifluoro-2-heptanone introduces strongly hydrophobic fluorinated groups into the main chain of the ether-free polymer, while the hydrophilic segment introduces strongly hydrophilic diionic functional groups, which synergistically increase the thermodynamic incompatibility between the hydrophilic and hydrophobic segments, further promote hydrophilic-hydrophobic microphase separation, and promote ion transmission. By controlling the length of the hydrophilic and hydrophobic chain segments, the width and connectivity of the ion domains in the microphase separation can be effectively regulated, providing a "wide and unobstructed" path for the efficient transmission of ions and improving ionic conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of the performance improvement of the fluorine-containing microblock polyarylalkyl anion exchange membrane of the present invention;
[0022] Figure 2 It is a schematic diagram of the chemical synthesis of the fluorine-containing microblock polyarylalkyl anion exchange membrane and the random copolymer anion exchange membrane QPBPF-r of the present invention;
[0023] Figure 3 The fluorinated microblock polyaralkyl copolymer, the random copolymer PBPF-r, and the quaternized fluorinated microblock polyaralkyl copolymer of Example 1 of the present invention are 1 H NMR spectra;
[0024] Figure 4 is a GPC curve diagram of the oligomers in Examples 1 and 2 of the present invention;
[0025] Figure 5 is a GPC curve diagram of the fluorine-containing polyarylalkyl copolymer in Example 1, Example 2 and Comparative Example 1 of the present invention;
[0026] Figure 6 It is a curve diagram of the water content and swelling rate of the anion exchange membranes of Examples 1, 2 and 3 of the present invention and the random copolymer anion exchange membrane of Comparative Example 1 as a function of temperature;
[0027] Figure 7 It is a comparison diagram of the mechanical properties of the anion exchange membranes of Examples 1 and 2 of the present invention and the random copolymer anion exchange membrane of Comparative Example 1;
[0028] Figure 8 It is a transmission electron microscope comparison diagram of the anion exchange membranes of Examples 1, 2 and 3 of the present invention and the random copolymer anion exchange membrane of Comparative Example 1;
[0029] Fig. 9It is an atomic force microscope comparison diagram of the anion exchange membranes of Examples 1, 2 and 3 of the present invention and the random copolymer anion exchange membrane of Comparative Example 1;
[0030] Fig.10 is a small angle X-ray scattering comparison diagram of anion exchange membranes of Example 1 and Example 2 of the present invention;
[0031] Fig.11 The OH of the anion exchange membranes of Examples 1, 2, and 3 of the present invention and the random copolymer anion exchange membrane of Comparative Example 1 at different temperatures - Conductivity comparison chart. DETAILED DESCRIPTION
[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. Although certain embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be interpreted as being limited to the embodiments described herein. On the contrary, these embodiments are provided to provide a more thorough and complete understanding of the present invention. It should be understood that the drawings and embodiments of the present invention are only for exemplary purposes and are not intended to limit the scope of protection of the present invention.
[0033] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by those skilled in the art to which this application belongs; the terms used in the specification of this application are only for the purpose of describing specific implementation methods and are not intended to limit this application;
[0034] The term "including" and its variations used in this article are open inclusions, that is, "including but not limited to"; the term "based on" is "based at least in part on"; the term "one embodiment" means "at least one embodiment"; the term "another embodiment" means "at least one other embodiment"; the term "some embodiments" means "at least some embodiments"; the term "optionally" means "optional embodiments". The relevant definitions of other terms will be given in the following description. It should be noted that the concepts of "first" and "second" mentioned in the present invention are used to distinguish different objects, rather than to describe a specific order or a primary and secondary relationship. In addition, the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, unless otherwise specified, the meaning of "multiple" is two or more.
[0035] In view of the problems existing in the above-mentioned related technologies, this embodiment provides a fluorine-containing micro-segmented polyarylalkyl anion exchange membrane and a preparation method thereof.
[0036] The present invention provides a method for preparing a fluorinated microblock polyarylalkyl anion exchange membrane, which specifically comprises the following steps:
[0037] S1: dissolving biphenyl and trifluoroacetone in dichloromethane, then adding a superacid catalyst in an ice bath, stirring and reacting for more than 2 hours to obtain a hydrophobic oligomer;
[0038] S2: dissolving biphenyl and 7-bromo-1,1,1,-trifluoro-2-heptanone in dichloromethane, then adding a superacid catalyst in an ice bath, stirring and reacting for more than 2 hours to obtain a hydrophilic oligomer;
[0039] S3: mixing the hydrophobic oligomer and the hydrophilic oligomer for reaction for more than 6 hours to obtain a block copolymer solution, adding methanol for precipitation, filtering out the precipitate, and obtaining a fluorine-containing microblock polyarylalkyl copolymer including a hydrophilic segment and a hydrophobic segment;
[0040] S4: dissolving the fluorinated micro-block polyarylalkyl copolymer in N-methylpyrrolidone, and then adding 6-dimethylhexylaminotrimethylammonium iodide, reacting for more than 20 hours, and grafting the hydrophilic segment with a diquaternary ammonium cationic side chain. After the reaction, pouring into anhydrous ether solution to precipitate, filtering, and obtaining a quaternized fluorinated micro-block polyarylalkyl polymer;
[0041] S5: dissolving the quaternized fluorinated microblock polyarylalkyl polymer in dimethyl sulfoxide to obtain a uniform polymer membrane liquid, coating the polymer membrane liquid uniformly on a flat plate and drying it to obtain a block copolymerized fluorinated microblock polyarylalkyl anion exchange membrane.
[0042] In this embodiment, the hydrophobic segment formed by the hydrophobic oligomer is used to maintain the mechanical strength of the anion exchange membrane (AEMs), and the hydrophilic segment formed by the hydrophilic oligomer is grafted with a diquaternary ammonium cationic side chain by adding 6-dimethylhexylaminotrimethylammonium iodide for OH - High-speed transmission of AEMs can be achieved by designing block copolymers of hydrophobic oligomers and hydrophilic oligomers, and the thermodynamic incompatibility between the hydrophilic and hydrophobic segments can be utilized to promote the microphase separation of AEMs and further improve the ionic conductivity. For the hydrophobic segment, the addition of trifluoroacetone and 7-bromo-1,1,1,-trifluoro-2-heptanone introduces strongly hydrophobic fluorinated groups into the main chain of the ether-free polymer, while the hydrophilic segment introduces strongly hydrophilic diionic functional groups, which synergistically increase the thermodynamic incompatibility between the hydrophilic and hydrophobic segments, further promote hydrophilic-hydrophobic microphase separation, and promote ion transmission. By controlling the length of the hydrophilic and hydrophobic chain segments, the width and connectivity of the ion domains in the microphase separation can be effectively regulated, providing a "wide and unobstructed" path for the efficient transmission of ions and improving ionic conductivity.
[0043] In this embodiment, the reaction in S4 needs to be heated at 60°C, and a high boiling point solvent and a reagent that can dissolve the polymer well need to be selected for the reaction. N-methylpyrrolidone can also be replaced with dimethyl sulfoxide solvent, and the reaction is carried out in dimethyl sulfoxide solvent. The casting method is selected in S5. It is necessary to select a high boiling point solvent that can dissolve the polymer. Select dimethyl sulfoxide solvent, and slowly evaporate at 60-80°C to obtain the required dense anion exchange membrane.
[0044] Specifically, the chemical formula for the preparation process of the fluorinated microblock polyarylalkyl anion exchange membrane is as follows: Figure 2 As shown, S1 is Figure 2 The chemical formula of the first line in the equation gives a hydrophobic oligomer, S2 is Figure 2 The chemical formula of the second row in the above formula is used to obtain a hydrophilic oligomer, and S3 is the chemical formula of the block copolymerization of the hydrophobic oligomer in the first row and the hydrophilic oligomer in the second row. Finally, a fluorinated microblock polyarylalkyl anion exchange membrane QPBPF-bm is obtained.
[0045] Figure 2 The third line is the chemical formula of the random copolymerization reaction, and the random copolymer anion exchange membrane QPBPF-r is obtained.
[0046] Optionally, in step S1, the longer the stirring reaction time is, the longer the length of the hydrophobic oligomer is; in step S2, the longer the stirring reaction time is, the longer the length of the hydrophilic oligomer is.
[0047] In this optional embodiment, by controlling the stirring reaction time and thereby controlling the chain segment lengths of the hydrophobic oligomers (i.e., the hydrophobic segment) and the hydrophilic oligomers (i.e., the hydrophilic segment), the microphase separation morphology and ion channel size of the synthesized alkaline anion exchange membrane can be regulated, thereby adjusting the ionic conductivity, water absorption, mechanical strength and other properties of the anion exchange membrane.
[0048] Alternatively, the super acid catalyst includes trifluoroacetic acid and trifluoromethanesulfonic acid.
[0049] In this optional embodiment, the super acid acts as a good catalyst, allowing some reactions that are difficult to carry out to be carried out under milder conditions, thereby simplifying the operation and reducing the operating cost.
[0050] Optionally, step S3 further includes: washing the precipitate with methanol for 3-5 times until the precipitate is neutral.
[0051] In this optional embodiment, after washing with methanol, the fluorine-containing micro-block polyarylalkyl copolymer is completely precipitated and other impurities can be washed away.
[0052] Optionally, the reaction is carried out at 60° C. for more than 20 hours in step S4.
[0053] In this optional embodiment, the hydrophilic segment is grafted with a diquaternary ammonium cationic side chain, and the number of cations is increased while the flexible chain is introduced, which is more conducive to the self-aggregation of the cationic groups, thereby making it easier to form a through ion transmission channel, while increasing the size of the ion domain and accelerating the OH - Ion transport rate.
[0054] Optionally, in step S5, the polymer film liquid is evenly coated on the flat plate and dried at 60-80° C. for 24 hours.
[0055] In this optional embodiment, the polymer film liquid can be evenly coated on a flat glass plate and dried at 60-80° C. for 24 hours. Increasing the temperature can speed up the drying process, and the film can be peeled off the glass plate.
[0056] Optionally, the method further comprises step S6: soaking the fluorinated micro-block poly(arylalkyl) anion exchange membrane in a 1M NaOH solution for more than 24 hours, and then washing with deionized water to obtain a hydroxide-type fluorinated micro-block poly(arylalkyl) anion exchange membrane.
[0057] In this optional embodiment, the hydroxide-type fluorinated microblock polyarylalkyl anion exchange membrane can be used for OH - High-speed transmission and improved ion conductivity.
[0058] A fluorinated microblock polyarylalkyl anion exchange membrane provided in an embodiment of the present invention is prepared according to the method for preparing a fluorinated microblock polyarylalkyl anion exchange membrane as described above, and comprises a microblock polymer main chain consisting of a hydrophilic segment and a hydrophobic segment, wherein the hydrophilic segment is grafted with a diquaternary ammonium cation side chain.
[0059] Optionally, the lengths of the hydrophilic segment and the hydrophobic segment are regulated to increase the thermodynamic incompatibility between the hydrophilic segment and the hydrophobic segment, thereby regulating the microphase separation morphology and ion channel size of the fluorinated microblock polyarylalkyl anion exchange membrane.
[0060] In this optional embodiment, the hydrophilic segment and the hydrophobic segment have different lengths, which can effectively regulate the microphase separation morphology and ion channel size of the synthetic alkaline anion exchange membrane, thereby adjusting the ionic conductivity, water absorption, mechanical strength and other properties of the anion exchange membrane.
[0061] Optionally, the molecular formula of the quaternized fluorinated microblock polyaralkyl polymer is
[0062]
[0063] Wherein x is the percentage of the hydrophobic segment in the polymer main chain, 1-x is the percentage of the hydrophilic segment in the polymer main chain, and n is an integer greater than 2.
[0064] In this embodiment, by designing the block copolymerization of hydrophobic oligomers and hydrophilic oligomers, the thermodynamic incompatibility between the hydrophilic segment and the hydrophobic segment can be utilized to increase the microphase separation structure of AEMs and improve the ionic conductivity; the hydrophilic segment formed by the hydrophilic oligomer is grafted with a diquaternary ammonium cationic side chain for OH - High-speed transmission further improves ionic conductivity.
[0065] Optionally, the tensile strength is 25.2-27.5 MPa, and the elongation at break is 12.6-14.9%.
[0066] In this optional embodiment, the elongation at break of the anion exchange membrane is improved, and the mechanical properties also meet the application requirements of fuel cells.
[0067] Optionally, OH at 30°C - The conductivity is 28.76-42.50mS / cm. As the temperature rises to 80℃, OH - The conductivity increased to 94.49-132.70 mS / cm.
[0068] In this optional embodiment, the conductivity of the membrane increases with increasing temperature, which is caused by the mobility of anions increasing with temperature. The conductivity of the anion exchange membrane tends to increase with temperature more obviously, which corresponds to the phase separation morphology of the membrane, with large ion channels, which is conducive to ion transport and high conductivity.
[0069] The present invention is further described below in conjunction with specific embodiments.
[0070] Example 1, a method for preparing a short-chain fluorine-containing microblock polyarylalkyl anion exchange membrane, the steps of which are as follows:
[0071] (1) Preparation of short-chain fluorinated microblock arylalkyl copolymer PBPF-b2.
[0072] 0.027 g of biphenyl and 0.018 mL of trifluoroacetone were dissolved in 0.410 mL of anhydrous dichloromethane, and 0.054 mL of trifluoroacetic acid and 0.390 mL of trifluoromethanesulfonic acid were added under ice bath, and stirred for reaction for 2 hours under ice bath to obtain oligomer O-PBF-2; 0.060 g of biphenyl and 0.082 mL of 7-bromo-1,1,1,-trifluoro-2-heptanone were dissolved in 0.620 mL of anhydrous dichloromethane, and added under ice bath. 0.054 mL of trifluoroacetic acid and 0.560 mL of trifluoromethanesulfonic acid were added, and the mixture was stirred and reacted for 2 hours under ice bath to obtain oligomer O-PBF-Br2; the two reaction solutions were then directly blended and reacted at room temperature for about 6 hours; after the reaction, the reddish brown viscous polymer was poured into a methanol solution for precipitation to obtain a light yellow block product, which was filtered and washed with a methanol solution for three to five times until neutral to obtain a short-chain fluorinated micro-block aralkyl copolymer PBPF-b2, which was dried for standby use;
[0073] (2) Preparation of quaternized short-chain fluorinated micro-block aromatic alkyl copolymer QPBPF-b2.
[0074] 0.1 g of the fluorinated aralkyl copolymer obtained in step (1) was dissolved in 5 mL of N-methylpyrrolidone, 58 mg of 6-dimethylhexylaminotrimethylammonium iodide was added, and the mixture was reacted at 60° C. for 20 h, and then precipitated in 40 mL of anhydrous ether, washed, and filtered to obtain a quaternized short-chain fluorinated micro-block aralkyl copolymer;
[0075] (3) Preparation of short-chain fluorinated microblock polyarylalkyl anion exchange membrane QPBPF-b2.
[0076] Take 0.1 g of the quaternized fluorinated microblock polyarylalkyl polymer obtained in step (2) and dissolve it in 5 mL of dimethyl sulfoxide to obtain a uniform polymer membrane liquid, and evenly coat the membrane liquid on a flat glass plate, dry it at 60°C for 24 h, peel off the membrane from the glass plate, and then soak it in 1M NaOH solution for 24 h, wash the film with deionized water to remove excess sodium hydroxide, and obtain a hydroxide-type QPBPF-b2 anion exchange membrane.
[0077] Example 2, a method for preparing a long-chain fluorine-containing microblock polyarylalkyl anion exchange membrane, the steps of which are as follows:
[0078] (1) Preparation of long-chain fluorinated microblock arylalkyl copolymer PBPF-b10.
[0079] 0.027 g of biphenyl and 0.018 mL of trifluoroacetone were dissolved in 0.410 mL of anhydrous dichloromethane, and 0.054 mL of trifluoroacetic acid and 0.390 mL of trifluoromethanesulfonic acid were added under ice bath, and stirred for 10 hours under ice bath to obtain oligomer O-PBF-10; 0.060 g of biphenyl and 0.082 mL of 7-bromo-1,1,1,-trifluoro-2-heptanone were dissolved in 0.620 mL of anhydrous dichloromethane, and added under ice bath. 0.054 mL of trifluoroacetic acid and 0.560 mL of trifluoromethanesulfonic acid were stirred and reacted in an ice bath for 10 hours to obtain an oligomer O-PBF-Br10; the two reaction solutions were then directly blended and reacted at room temperature for about 8 hours; after the reaction, the reddish-brown viscous polymer was poured into a methanol solution for precipitation to obtain a light yellow block product, which was filtered and washed with a methanol solution for three to five times until neutral to obtain a long-chain fluorinated micro-block aralkyl copolymer PBPF-b10, which was dried for standby use;
[0080] (2) Preparation of quaternary ammonium fluorinated microblock arylalkyl copolymer QPBPF-b10.
[0081] 0.1 g of the long-chain fluorinated micro-block aralkyl copolymer obtained in step (1) was dissolved in 5 mL of N-methylpyrrolidone, 58 mg of 6-dimethylhexylaminotrimethylammonium iodide was added, and the mixture was reacted at 60° C. for 20 h, and then precipitated in 40 mL of anhydrous ether, washed, and filtered to obtain a quaternized fluorinated micro-block polyaralkyl polymer;
[0082] (3) Preparation of long-chain fluorinated microblock polyarylalkyl anion exchange membrane QPBPF-b10.
[0083] Take 0.1 g of the quaternized fluorinated microblock polyarylalkyl polymer obtained in step (2) and dissolve it in 5 mL of dimethyl sulfoxide to obtain a uniform polymer membrane liquid, and evenly coat the membrane liquid on a flat glass plate, dry it at 60°C for 24 h, peel the membrane off the glass plate, and then soak it in 1M NaOH solution for 24 h, wash the film with deionized water to remove excess sodium hydroxide, and obtain a hydroxide-type QPBPF-b10 anion exchange membrane.
[0084] Example 3, a method for preparing a long-chain fluorine-containing microblock polyarylalkyl anion exchange membrane, the steps of which are as follows:
[0085] (1) Preparation of long-chain fluorinated microblock arylalkyl copolymer PBPF-b20.
[0086] 0.027 g of biphenyl and 0.018 mL of trifluoroacetone were dissolved in 0.410 mL of anhydrous dichloromethane, and 0.054 mL of trifluoroacetic acid and 0.390 mL of trifluoromethanesulfonic acid were added under ice bath, and stirred for reaction for 20 hours under ice bath to obtain oligomer O-PBF-20; 0.060 g of biphenyl and 0.082 mL of 7-bromo-1,1,1,-trifluoro-2-heptanone were dissolved in 0.620 mL of anhydrous dichloromethane, and added under ice bath. 0.054 mL of trifluoroacetic acid and 0.560 mL of trifluoromethanesulfonic acid were stirred and reacted in an ice bath for 20 hours to obtain an oligomer O-PBF-Br20; the two reaction solutions were then directly blended and reacted at room temperature for about 8 hours; after the reaction, the reddish-brown viscous polymer was poured into a methanol solution for precipitation to obtain a light yellow block product, which was filtered and washed with a methanol solution for three to five times until neutral to obtain a long-chain fluorinated micro-block aralkyl copolymer PBPF-b20, which was dried for standby use;
[0087] (2) Preparation of quaternized long-chain fluorinated microblock aralkyl copolymer QPBPF-b20
[0088] 0.1 g of the fluorinated micro-block aralkyl copolymer obtained in step (1) was dissolved in 5 mL of N-methylpyrrolidone, 58 mg of 6-dimethylhexylaminotrimethylammonium iodide was added, and the mixture was reacted at 60° C. for 20 h, and then precipitated in 40 mL of anhydrous ether, washed, and filtered to obtain a quaternized fluorinated micro-block aralkyl copolymer;
[0089] (3) Preparation of long-chain fluorinated microblock polyarylalkyl anion exchange membrane QPBPF-b20
[0090] Take 0.1 g of the quaternized fluorinated microblock polyarylalkyl polymer obtained in step (2) and dissolve it in 5 mL of dimethyl sulfoxide to obtain a uniform polymer membrane liquid, and evenly coat the membrane liquid on a flat glass plate, dry it at 60°C for 24 h, peel the membrane off the glass plate, and then soak it in 1M NaOH solution for 24 h, wash the film with deionized water to remove excess sodium hydroxide, and obtain a hydroxide-type QPBPF-b20 anion exchange membrane.
[0091] Comparative Example 1, a method for preparing a random copolymer anion exchange membrane PBPF-r, the steps are as follows:
[0092] (1) Preparation of random copolymer PBPF-r.
[0093] 0.087 g of biphenyl, 0.018 mL of trifluoroacetone, and 0.082 mL of 7-bromo-1,1,1,-trifluoro-2-heptanone were dissolved in 1.030 mL of anhydrous dichloromethane, and 0.108 mL of trifluoroacetic acid and 0.950 mL of trifluoromethanesulfonic acid were added under ice bath, and stirred for reaction for 10 hours under ice bath; after the reaction, the reddish brown viscous polymer was poured into methanol solution for precipitation to obtain a light yellow block product, the product was filtered, and washed with methanol solution for three to five times until neutral to obtain a random copolymer PBPF-r, which was dried for standby use;
[0094] (2) Preparation of quaternary ammonium random copolymer QPBPF-r.
[0095] 0.1 g of the random copolymer PBPF-r obtained in step (1) was dissolved in 5 mL of N-methylpyrrolidone, 58 mg of 6-dimethylhexylaminotrimethylammonium iodide was added, and the mixture was reacted at 60° C. for 20 h, and then precipitated in 40 mL of anhydrous ether, washed, and filtered to obtain a quaternary random copolymer QPBPF-r;
[0096] (3) Preparation of random copolymer anion exchange membrane QPBPF-r.
[0097] Take 0.1 g of the quaternized random copolymer QPBPF-r obtained in step (2) and dissolve it in 5 mL of dimethyl sulfoxide to obtain a uniform polymer membrane liquid, and evenly coat the membrane liquid on a flat glass plate, dry it at 60°C for 24 hours, peel the membrane off the glass plate, and then soak it in 1M NaOH solution for 24 hours, wash the film with deionized water to remove excess sodium hydroxide, and obtain a hydroxide-type random copolymer anion exchange membrane QPBPF-r.
[0098] Figure 1 The hydrophilic and hydrophobic block structures and OH groups of the fluorinated polyarylalkyl anion exchange membranes prepared in Examples 1, 2 and 3 are shown in FIG. - Schematic diagram of ion transport. The data characterization diagram confirms that the design of this structure is beneficial to the performance improvement of anion exchange membrane.
[0099] Figure 3The nuclear magnetic resonance hydrogen spectrum of the polymers PBPF-b2 and QPBPF-b2 obtained in steps (1) and (2) of this embodiment 1 and the random copolymer PBPF-r obtained in comparative example 1, specific data: the characteristic peak of H of the benzene ring on biphenyl appears at 7.3-7.8ppm, the methyl peak of trifluoroacetone appears at 2.0ppm, and the methylene peak on 7-bromo-1,1,1,-trifluoro-2-heptanone appears at 2.45, 1.43, 1.25, 1.79, and 3.32ppm, respectively. After calculating the integrals of the two peaks 3 and 8, and the above-mentioned nuclear magnetic resonance, the successful synthesis of PBPF-b2 is proved. It can be observed from the peaks in the aromatic region that PBPF-b2 is split compared to the aromatic region of PBPF-r. Once again, the successful synthesis of the block polymer is confirmed. After quaternization with an excess of 6-dimethylhexylaminotrimethylammonium iodide, the two cations of the PBPF-b2 polymer are converted into QPBPF-b2 polymers through quaternization reaction. As can be seen from the figure, the methylene peak on the side chain is enhanced, and the methylene peak of the C-Br bond at 2.45 ppm disappears, proving the successful synthesis of QPBPF-b2 polymer.
[0100] Figure 4 The molecular weights of the O-PBF-2 and O-PBF-Br2 oligomers prepared in Example 1 and the O-PBF-10 and O-PBF-Br10 oligomers prepared in Example 2 are compared by GPC. Figure 4 As shown in the figure, with the increase of reaction time, the molecular weight of the oligomer increases and the length of the chain segment increases. It is confirmed that the fluorinated microblock polyarylalkyl anion exchange membrane with different chain lengths is successfully prepared.
[0101] Figure 5 The molecular weight comparison of the GPC of the QPBPF-b2 polymer prepared in Example 1 and the QPBPF-b10 polymer prepared in Example 2 is shown in FIG. Figure 5 As shown in Figure 2, the molecular weight of the polymer can be as high as 108.6 kg / mol. The larger the molecular weight, the better the film-forming property of AEMs can be ensured, and it is also beneficial to improve the mechanical properties of the membrane.
[0102] Figure 6The water dissolution and expansion resistance of the QPBPF-b2 anion exchange membrane prepared in Example 1, the QPBPF-b10 anion exchange membrane prepared in Example 2, the QPBPF-b20 anion exchange membrane prepared in Example 3, and the random copolymer anion exchange membrane PBPF-r prepared in Comparative Example 1 were characterized. The QPBPF-b2, QPBPF-b10 and QPBPF-b20 anion exchange membranes were placed in glass bottles filled with water at a certain temperature and soaked for 24 hours, and the moisture content and linear swelling rate of the membranes were measured. The moisture content of the membrane QPBPF-b2 was 35.8wt% and the linear swelling rate was 15.9% at 30°C. When the temperature was raised to 80°C, its moisture content and linear swelling rate were 77.9wt% and 33.1%, respectively. The moisture content of the membrane QPBPF-b10 was 46.6wt% and the linear swelling rate was 14.5% at 30°C. When the temperature was raised to 80°C, its moisture content and linear swelling rate were 85.3wt% and 35.7%, respectively. The moisture content of the membrane QPBPF-b20 was 47.80wt% and the linear swelling rate was 15.3% at 30°C. When the temperature was raised to 80°C, its moisture content and linear swelling rate were 90wt% and 38.7%, respectively. Figure 6 It can be seen that the water content and linear swelling rate of the anion exchange membrane increase with the increase of temperature, and the long-chain microblock structure is conducive to the aggregation of cations, thereby increasing the water content. The water absorption rate of the two block membranes is higher than that of the random copolymer membrane. At the same time, the fluorinated microblock structure ensures the dimensional stability of the membrane and the mechanical integrity of the membrane when the fuel cell is running at high temperature.
[0103] Figure 7 The mechanical properties of the QPBPF-b2 anion exchange membrane prepared in Example 1, the QPBPF-b10 anion exchange membrane prepared in Example 2, and the random copolymer anion exchange membrane PBPF-r prepared in Comparative Example 1 were characterized. The changes in the tensile strength (Ts) and elongation at break (Eb) of the membranes are shown in Figure 1. Figure 7 As shown. The tensile strength of the QPBPF-b2 membrane prepared in Example 1 is 27.5MPa, and the elongation at break is 12.6%; the tensile strength of the QPBPF-b10 membrane prepared in Example 2 is 25.2MPa, and the elongation at break is 14.9%; the long-chain microblock structure is conducive to the entanglement of the flexible side chains, thereby improving the elongation at break of the membrane, and the mechanical properties also meet the requirements of fuel cell applications. At the same time, the mechanical strength and elongation at break of the two-block membranes of Example 1 and Example 2 are both higher than those of the random copolymer membrane of Comparative Example 1.
[0104] Figure 8Transmission electron microscopy (TEM) was used to characterize the microphase separation morphology of the anion exchange membranes of Examples 1 and 2 of the present invention, the QPBPF-b20 anion exchange membrane prepared in Example 3, and the random copolymer anion exchange membrane of Comparative Example 1. Figure 8 It can be clearly seen that the QPBPF-b10 anion exchange membrane prepared in this Example 2 has a clearer hydrophilic-hydrophobic microphase separation morphology than the membrane prepared in Example 1. At the same time, due to the structural design of the separation of the hydrophilic segment and the hydrophobic segment, it is more conducive to the self-aggregation of cations, and the hydrophilic regions are interconnected, providing an unobstructed channel for the transmission of ions, thereby improving the ion transmission efficiency, thereby improving the conductivity of the anion exchange membrane, and the hydrophobic region provides mechanical support for the anion exchange membrane, ensuring the mechanical stability of the membrane. Among them, QPBPF-b20 has the most obvious microphase separation structure, which confirms the benefit of segment growth for performance improvement.
[0105] Fig. 9 The anion exchange membranes of Examples 1, 2, and 3 of the present invention and the random copolymer anion exchange membrane of Comparative Example 1 were characterized by atomic force microscopy (AFM). Fig. 9 It can be clearly seen that the anion exchange membranes prepared in Examples 1, 2 and 3 of the invention all have different degrees of microphase separation morphology. With the increase of the length of the microblock chain segment, the microphase separation structure of the AEMs gradually becomes clear. This is because the growth of the hydrophilic chain segment is conducive to the aggregation of cations to form a hydrophilic region, thereby forming a huge hydrophilicity difference with the hydrophobic segment. The polarity difference between the hydrophilic end and the hydrophobic end can drive the self-aggregation of the polymer, thereby forming a phase separation structure in the AEMs, which is consistent with the transmission result.
[0106] Fig.10 The anion exchange membranes of Example 1 and Example 2 of the present invention were subjected to small angle X-ray scattering tests respectively. Fig.10 It can be seen that the polymer of Example 1QPBPF-b2 has a -1 A broad peak appears at q = 0.3 nm. According to the Bragg equation d = 2π / q, the hydrophilic region size is 6.24 nm. -1 A broad peak appears at , and according to the Bragg equation d = 2π / q, the hydrophilic region size is 20.9nm, which corresponds to the AFM result. Therefore, appropriately increasing the length of the microblock chain segment and expanding the microphase separation size is conducive to promoting the formation of a hydrophilic / hydrophobic microphase separation structure.
[0107] Fig.11 The OH values of the anion exchange membranes of Examples 1, 2 and 3 of the present invention and the random copolymer anion exchange membrane of Comparative Example 1 at different temperatures were- The conductivity of QPBPF-b2 anion exchange membrane was measured at 30℃. - The conductivity is 28.76mS / cm. As the temperature rises to 80℃, OH - The conductivity of QPBPF-b10 anion exchange membrane increased to 94.49mS / cm. - The conductivity is 40.44mS / cm. As the temperature rises to 80℃, OH - The conductivity of QPBPF-b20 anion exchange membrane increased to 124.72mS / cm. - The conductivity is 42.50mS / cm. As the temperature rises to 80℃, OH - The conductivity increased to 132.70mS / cm. It can be seen that the conductivity of the membrane increases with the increase of temperature, which is caused by the increase of the mobility of anions with temperature. The conductivity of the QPBPF-b20 anion exchange membrane changes more obviously with the increase of temperature than that of the QPBPF-b10, and the conductivity of the QPBPF-b10 anion exchange membrane changes more obviously with the increase of temperature than that of the QPBPF-b2, which corresponds to the phase separation morphology of the membrane, that is, the growth of the block chain segment makes the formed ion channel larger, which is conducive to ion transport. And the conductivity is higher than that of the random copolymer anion exchange membrane.
[0108] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A method for preparing a fluorinated microblock polyarylalkyl anion exchange membrane, characterized in that: The specific steps include: S1: dissolving biphenyl and trifluoroacetone in dichloromethane, then adding a superacid catalyst in an ice bath, stirring and reacting for more than 2 hours to obtain a hydrophobic oligomer; S2: dissolving biphenyl and 7-bromo-1,1,1,-trifluoro-2-heptanone in dichloromethane, then adding a superacid catalyst in an ice bath, stirring and reacting for more than 2 hours to obtain a hydrophilic oligomer; S3: mixing the hydrophobic oligomer and the hydrophilic oligomer for reaction for more than 6 hours to obtain a block copolymer solution, adding methanol for precipitation, filtering out the precipitate, and obtaining a fluorine-containing microblock polyarylalkyl copolymer including a hydrophilic segment and a hydrophobic segment; S4: dissolving the fluorinated micro-block polyarylalkyl copolymer in N-methylpyrrolidone, and then adding 6-dimethylhexylaminotrimethylammonium iodide to react for more than 20 hours, wherein the hydrophilic segment is grafted with a diquaternary ammonium cationic side chain, and after the reaction is completed, pouring into anhydrous ether solution to precipitate, filtering, and obtaining a quaternized fluorinated micro-block polyarylalkyl polymer; S5: dissolving the quaternized fluorinated microblock polyarylalkyl polymer in dimethyl sulfoxide to obtain a uniform polymer membrane liquid, coating the polymer membrane liquid uniformly on a flat plate and drying it to obtain a block copolymerized fluorinated microblock polyarylalkyl anion exchange membrane.
2. The method for preparing a fluorinated microblock polyarylalkyl anion exchange membrane according to claim 1, characterized in that: In the step S1, the longer the stirring reaction time is, the longer the length of the hydrophobic oligomer is; in the step S2, the longer the stirring reaction time is, the longer the length of the hydrophilic oligomer is.
3. The method for preparing a fluorinated microblock polyarylalkyl anion exchange membrane according to claim 1, characterized in that: Step S3 also includes: washing the precipitate with methanol for 3-5 times until the precipitate is neutral.
4. The method for preparing a fluorinated microblock polyarylalkyl anion exchange membrane according to claim 1, characterized in that: In step S4, the reaction is carried out at 60° C. for more than 20 hours.
5. The method for preparing a fluorinated microblock polyarylalkyl anion exchange membrane according to claim 1, characterized in that: In step S5, the polymer film liquid is evenly coated on the flat plate and dried at 60-80° C. for more than 24 hours.
6. The method for preparing a fluorinated microblock polyarylalkyl anion exchange membrane according to claim 1, characterized in that: The method further comprises step S6: soaking the fluorinated micro-block poly(arylalkyl) anion exchange membrane in a 1M NaOH solution for more than 24 hours, and then washing with deionized water to obtain a hydroxide-type fluorinated micro-block poly(arylalkyl) anion exchange membrane.
7. A fluorinated microblock polyarylalkyl anion exchange membrane, characterized in that: The fluorinated microblock polyarylalkyl anion exchange membrane is prepared according to the preparation method of any one of claims 1 to 6, comprising a microblock polymer main chain consisting of a hydrophilic segment and a hydrophobic segment, wherein the hydrophobic segment contains superhydrophobic fluorine, and the hydrophilic segment is grafted with a diquaternary ammonium cationic side chain.
8. The fluorinated microblock polyarylalkyl anion exchange membrane according to claim 7, characterized in that: The length regulation of the hydrophilic segment and the hydrophobic segment can increase the thermodynamic incompatibility between the hydrophilic segment and the hydrophobic segment, and regulate the microphase separation morphology and ion channel size of the fluorine-containing micro-segmented polyarylalkyl anion exchange membrane.
9. The fluorinated microblock polyarylalkyl anion exchange membrane according to claim 7, characterized in that: The tensile strength is 25.2-27.5MPa and the elongation at break is 12.6-14.9%.
10. The fluorinated microblock polyarylalkyl anion exchange membrane according to claim 7, characterized in that: OH at 30℃ - The conductivity is 28.76-42.50 mS / cm. As the temperature rises to 80°C, the OH - The conductivity increased to 94.49-132.70 mS / cm.